LA DEFENSA DEL CONTRIBUYENTE ANTE LAS AUTORIDADES FISCALES EN MÉXICO - Grajeda Grajeda, Rebeca Patricia (UNIVERSIDAD DE SONORA, 2022)
This article addresses the issue of taxpayer defense. Its objective is to describe the tools contained in ordinary laws, the purpose of which is to provide citizens with expeditious and total access to the solution of disputes arising from their interaction with the tax authorities. It is a documentary and descriptive investigation on the administrative resources and the jurisdictional means of defense brought before arbitrary acts of the tax authorities, as well as the results obtained by the Tax Administration Service in the lawsuits filed against them from 2013 to the first semester of 2021, concluding that most of the errors made by the authority and that lead them to lose these lawsuits, are related to deficiencies of form and substance, for example: deficiencies in the notification of tax credits, in motivation, in the interpretation and in the writing of the minutes, among others reasons.